Ultrasensitive broadband photodetectors based on two-dimensional Bi2O2Te films - Vincent Teng (Journal of Materials Chemistry C, 2021)
Two-dimensional (2D) materials exhibit many unique optical and electronic properties that are highly desirable for application in optoelectronics. Here, we report the study of photodetector based on 2D Bi2O2Te grown on n-Si substrate. The 2D Bi2O2Te material was transformed from sputtered Bi2Te3 ultrathin film after rapid annealing at 400 ℃ for 10 min in air atmosphere. The photodetector was capable of detecting a broad wavelength from 210 nm to 2.4 μm with excellent responsivity of up to 3x105 and 2x104 AW-1, and detectivity of 4x1015 and 2x1014 Jones at deep ultraviolet (UV) and short-wave infrared (SWIR) under weak light illumination, respectively. The effectiveness of 2D materials in weak light detection was investigated by analysis of the photocurrent density contribution. Importantly, the facile growth process with low annealing temperature would allow direct large-scale integration of the 2D Bi2O2Te materials with complementary metal-oxide–semiconductor (CMOS) technology.